Pathogenesis and General Management of Disseminated Intravascular Coagulation - Barnoyev Saidjon Sharifovich; Sharopov Umarxo`ja Ravshanovich (Genius Journals, 2023)
Systemic intravascular activation of coagulation, which results in the deposition of fibrin in the circulation, is the hallmark of disseminated intravascular coagulation (DIC), an acquired syndrome that develops during severe illnesses
Keywords: Disseminated intravascular coagulation; Bleeding; Tissue factor